Homozygous mutation in the Neurofascin gene affecting the glial isoform of Neurofascin causes severe neurodevelopment disorder with hypotonia, amimia and areflexia. (13th August 2018) - Smigiel, Robert; Sherman, Diane L; Rydzanicz, Małgorzata; Walczak, Anna; Mikolajkow, Dorota; Krolak-Olejnik, Barbara; Kosińska, Joanna; Gasperowicz, Piotr; Biernacka, Anna; Stawinski, Piotr; Marciniak, Malgorzata; Andrzejewski, Witalij; et al.
Abstract: The Neurofascins (NFASCs) are a family of proteins encoded by alternative transcripts of NFASC that cooperate in the assembly of the node of Ranvier in myelinated nerves. Differential expression of NFASC in neurons and glia presents a remarkable example of cell-type specific expression of protein isoforms with a common overall function. In mice there are three NFASC isoforms: Nfasc186 and Nfasc140, located in the axonal membrane at the node of Ranvier, and Nfasc155, a glial component of the paranodal axoglial junction. Nfasc186 and Nfasc155 are the major isoforms at mature nodes and paranodes, respectively. Conditional deletion of the glial isoform Nfasc155 in mice causes severe motor coordination defects and death at 16–17 days after birth. We describe a proband with severe congenital hypotonia, contractures of fingers and toes, and no reaction to touch or pain. Whole exome sequencing revealed a homozygous NFASC variant chr1:204953187-C>T (rs755160624). The variant creates a premature stop codon in 3 out of four NFASC human transcripts and is predicted to specifically eliminate Nfasc155 leaving neuronal Neurofascin intact. The selective absence of Nfasc155 and disruption of the paranodal junction was confirmed by an immunofluorescent study of skin biopsies from the patient versus control. We propose that the disease in our proband is the first reported example of genetic deficiency of glial Neurofascin isoforms in humans and that the severity of the condition reflects the importance of the Nfasc155 in forming paranodal axoglial junctions and in determining the structure and function of the node of Ranvier.